The Correction of GPS Handy Receiver Deviation Using a Fixed Receiver - Marjan Nowrouzi; Hossein Navid; Mohammad Shahkar; Zahra Heidariyan (نشریه جغرافیا و برنامه‌ریزی, 2012)
The high cost of high accuracy GPS receivers and also lack of easy access to them has made limited the possibility of using the benefits of precision agriculture equipments in Iran. In this research, a new method in was studied to correct the deviation of low-cost non-differential receivers. For this case, two tests were performed. A fixed receiver determines the coordinates of fixed station and a mobile receiver went in route and was recording the points’ coordination in different time distances. After data processing, the route point map of mobile receiver was drawn, and by comparing the fixed receiver coordinates with the reference points, the deviation was determined. Then this deviation applied on mobile receiver data. Corrected path was drawn and the path before correction and the actual route was compared. To evaluate the effect of the time and speed on the creation and interpretation of data, the test was performed in 10 days and two speeds. Results showed that using this method, deviation of GPS was reduced 46 cm or 15%. Also, difference in deviation rates in different times of the days before and after correction, were significant.